Almutwatue with Alusoolieen and its Fiqh applycation - Al-Ghamari, Ibrahim Rashid Saif (Journal of Islamic Sciences, 2020)
The study of terms and indication and what the rules related to it is the most essential study in radical science which has got a large attention by radical scientists due to its strong relation with Shareia sources (holly Quran and Alsunat). One of the terms is “Almutwatue” -the topic of the research-. The purpose of it is to show up the scientists' efforts to justify the radical terms is scientific pattern with a supporting by Fiqhi applications. The study depends on analysing and comparing method between radical scientists' views, as well as bifurcation method. The study includes analysing some Quran interpreting books, Hadeeth explanations, and Fiqhi wrotes to find out the Fiqhi applications of Almutwatue and to show the researcher's point of view. One of the most important result is that ALmutwatue is a comprehensive term that includes sub terms in the same level, like the word human in term of humanity which include male and female in the same level. And it is very close to the terms Almushtarek and Almushakkek which indecates of generality of every things which is under its meaning, and indicates its generality very clearly. Radical scientists, interpreters, and Hadeeth explainers depend on it to be far from state of the generality of the term “Almushtarek” or aggregation between truth and metaphor. On this sheet, there is a review of Fiqhi examples of it.
Keywords: Agreement; truth; metaphor; Fundamentals of Fiqh